If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 = 7y + 8 Reorder the terms: -1 + 9x = 7y + 8 Reorder the terms: -1 + 9x = 8 + 7y Solving -1 + 9x = 8 + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9x = 8 + 1 + 7y Combine like terms: -1 + 1 = 0 0 + 9x = 8 + 1 + 7y 9x = 8 + 1 + 7y Combine like terms: 8 + 1 = 9 9x = 9 + 7y Divide each side by '9'. x = 1 + 0.7777777778y Simplifying x = 1 + 0.7777777778y
| (x-8)2+(y+7)2=225 | | 60h=270 | | 0.9(6x+4)=0.7-(x-3) | | 9x-1=3x+4t | | (x-6)2+(y-1)2=81 | | 15x=840 | | 186000=400X | | 10y+5x=500 | | 10y-5x=500 | | (x+4)2+(y-9)2=144 | | 3y-4=-14 | | -5x+3y=-47 | | 9x^6(9x^5-9)= | | 9x^5-9= | | 2.3b=1.5x | | 9a+54=80 | | 4x+-2+3x=12 | | 169x^4=0 | | 7x=3x+23 | | 44=-8X-45 | | 20+4g=5g | | 2(32+w)=120 | | y*x= | | x^2+12x-589=0 | | 2d-13d+4d+-11d=11 | | x^2=12x-589 | | 50+15+x=180 | | 12y=.25 | | 3(x+1)=6(x+6) | | 10y+32=82 | | 3cos(x)+9=7 | | 2.8x-0.4y+1.5=0 |